The effects of capsaicin and acidity on currents generated by noxious heat in cultured neonatal rat dorsal root ganglion neurones - Vlachová, V; Lyfenko, A; Orkand, R K; Vyklický, L (The Journal of physiology, 2001)
1. The effects of capsaicin, acidic pH, ATP, kainate and GABA on currents generated by noxious heat were studied in cultured dorsal root ganglion (DRG) neurones (< 20 microm in diameter) isolated from neonatal rats. The patch clamp technique was used to record membrane currents or changes of membrane potential. 2. In agreement with previous results, inward membrane currents (I(heat)) induced by a 3 s ramp of increasing temperature from room temperature (approximately 23 degrees C) to over 42 degrees C varied greatly between cells (-100 pA to -2.4 nA at 48 degrees C) and had a temperature coefficient (Q(10)) > 10 over the range of 43-52 degrees C. 3. Capsaicin potentiated the heat-induced current even when capsaicin, at room temperature, had little or no effect on its own. In cells in which capsaicin induced no or very small membrane current at room temperature (< 50 pA), I(heat) exhibited detectable activation above 40 degrees C and increased 5.1 +/- 1.1 (n = 37) and 6.3 +/- 2.0 (n = 18) times at 0.3 and 1 microM capsaicin, respectively. 4. A rapid decrease in extracellular pH from 7.3 to 6.8, 6.3 or 6.1 produced an inward current which inactivated in ~5 s either completely (pH 6.8 or 6.3) or leaving a small current (approximately 50 pA) for more than 2 min (pH 6.1). After inactivation of the initial low pH-induced current, I(heat) at 48 degrees C increased 2.3 +/- 0.4 times at pH 6.8, 4.0 +/- 0.6 times at pH 6.3 and 4.8 +/- 0.8 times at pH 6.1 with a Q(10) > 10 (n = 16). 5. ATP (n = 22), kainate (n = 7) and GABA (n = 8) at 100 microM, produced an inactivating inward current in all heat-sensitive DRG neurones tested. During inactivation and in the presence of the drug, I(heat) was increased slightly with ATP and unaffected with kainate and GABA. These agents apparently do not directly affect the noxious heat receptor. 6. The results indicate a novel class of capsaicin-sensitive cells, in which capsaicin evokes no or very small inward current but nevertheless increases sensitivity to noxious heat.
Keywords: Nociceptors; kultivované buňky; Ganglia, Spinal; metoda terčíkového zámku; Rats; neurony aferentní; extracelulární prostor; koncentrace vodíkových iontů; elektrická vodivost; vysoká teplota; kapsaicin; nociceptory; Patch-Clamp Techniques; Extracellular Space; krysa rodu Rattus; Cells, Cultured; Neurons, Afferent; zvířata; Hydrogen-Ion Concentration; Electric Conductivity; spinální ganglia; adenosintrifosfát; Hot Temperature; Kainic Acid; kyseliny; Acids; Capsaicin; Adenosine Triphosphate; kyselina kainová; Animals